Postmortem analysis of WWI human remains from Italian glaciers in rare environmental conditions - Daniel Gaudio; L. De Luca; V. Cirielli; M. Caccianiga; C. Bassi; N. Cappellozza; A. Galassi; F. Nicolis; C. Cattaneo (Archaeological and Anthropological Sciences, 2019)

Comparative pathogenicity study of ten different betanodavirus strains in experimentally infected E uropean sea bass, D icentrarchus labrax (L.) - N Vendramin; A Toffan; M Mancin; E Cappellozza; V Panzarin; G Bovo; G Cattoli; I Capua; C Terregino (Journal of Fish Diseases, 2014)
Viral encephalopathy and retinopathy ( VER ), otherwise known as viral nervous necrosis ( VNN ), is a severe pathological condition caused by RNA viruses belonging to the N odaviridae family, genus B etanodavirus . The disease, described in more than 50 fish species worldwide, is considered as the most serious viral threat affecting marine farmed species in the Mediterranean region, thus representing one of the bottlenecks for further development of the aquaculture industry. To date, four different genotypes have been identified, namely red‐spotted grouper nervous necrosis virus ( RGNNV ), striped jack nervous necrosis virus ( SJNNV ), tiger puffer nervous necrosis virus and barfin flounder nervous necrosis virus, with the RGNNV genotype appearing as the most widespread in the Mediterranean region, although SJNNV ‐type strains and reassortant viruses have also been reported. The existence of these genetically different strains could be the reason for the differences in mortality observed in the field. However, very little experimental data are available on the pathogenicity of these viruses in farmed fish. Therefore, in this study, the pathogenicity of 10 isolates has been assessed with an in vivo trial. The investigation was conducted using the European sea bass, the first target fish species for the disease in the Mediterranean basin. Naive fish were challenged by immersion and clinical signs and mortality were recorded for 68 days; furthermore, samples collected at selected time points were analysed to evaluate the development of the infection. Finally, survivors were weighed to estimate the growth reduction. The statistically supported results obtained in this study demonstrated different pathogenicity patterns, underlined the potential risk represented by different strains in the transmission of the infection to highly susceptible species and highlighted the indirect damage caused by a clinical outbreak of VER / VNN .

Viral encephalopathy and retinopathy outbreak in restocking facilities of the endangered freshwater species, S alaria fluviatilis (Asso) - N Vendramin; F Padrós; T Pretto; E Cappellozza; V Panzarin; G Bovo; A Toffan; C Terregino (Journal of Fish Diseases, 2012)